Foreword - St. Dennis, Marc (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2019)
It is my great pleasure to present the very first audiovisual edition of the First Peoples Child & Family Review! This is a peer reviewed journal dedicated to interdisciplinary knowledge honouring the voices and perspectives of First Nations, Métis, Inuit and other Indigenous people around the world. With this edition we want to highlight the importance of oral and visual knowledge transmission for Indigenous people. We want to challenge the prevalence of written knowledge transmission in academia and show that other ways of knowing are just as powerful. This includes publishing work from people young and old in recognition that learning is a lifelong journey and that each and every one of us carries wisdom in our hearts and in our minds. In total, there are 12 works published in this edition of the First Peoples Child & Family Review. This includes drawings and videos from Indigenous researchers, graduate students, community members, youth, and non-Indigenous allies and supporters. I want to thank all of the contributors to this special edition for sharing their knowledge, experience, and stories and to the peer referees for their thoughtful feedback. To you, the viewer, I hope you enjoy learning from and being inspired by the contributions that follow.